Food goes to war: 4-H and Extension during World War II - Sundgren, Katherine (Kansas State University, 2021)
4-H and the Extension Service were instrumental in the nationwide increase in food production that sustained the United States and its armed forces during World War II. At the onset of the war, the Extension Service distributed essential information at the national, state, and local levels through universities and the 4-H program. 4-H drew upon the intellectual and cultural tradition that they had cultivated to motivate and organize the food effort and help the Allies win the war. 4-H’s national influence and resources provided eager allies to war-oriented programs. The war had a lasting impact on 4-H as wartime programming and innovations stayed with the organization, leaving 4-H stronger than before. The aid provided by the 4-H program during the war was rewarded with greater funding from the national government, culminating in the Bankhead-Flannagan Act of 1945. This new funding allowed the 4-H program to continue to expand and impart intellectual and cultural traditions to future generations of 4-Hers. The 4-H and Extension that we know today were born of the exigencies of World War II.
Keywords: 4-H; Cooperative Extension Service; World War II; Agriculture; Food history